Development of the chromatographic fingerprint of herbal preparations Shuang-Huang-Lian oral liquid - Cao, Y.; Wang, L.; Yu, X.; Ye, J.
A simple, reliable and reproducible method, based on high performance liquid chromatography (HPLC), for developing chromatographic fingerprint of complex herbal medicine Shuang-Huang-Lian (SHL)oral liquid was described. Ten batches of SHL obtained from different pharmaceutical factories were used to establish the fingerprint. In addition, the contents of baicalin and chlorogenic acid, which are two marker constituents in the preparations, were also determined. Chromatographic fingerprint, together with the contents of the markers were applied for quality control of SHL. SHL comprises three kinds of medicinal herbs: Fols Lonicerae, Radix Scutellariae and Fructus Forsythiae. According to State Food and Drug Administration (SFDA)requirement, the chromatographic fingerprints of Fols Lonicerae, Radix Scutellariae and Fructus Forsythiae, the raw materials of SHL preparations, were also established. The data of fingerprints of SHL and its raw herbs established by HPLC were all processed with two kinds of mathematic methods including correlation coefficient and cosine value of vectorial angle to validate their similarities. In conclusion, fingerprints of Radix Scutellariae, Fols Lonicerae and Fructus Forsythiae are suitable for identification, differentiation of their geographic origins and quality control. The similarity of 10 batches of SHL oral liquid was more than 0.988, which showed the preparations from different pharmaceutical factories were consistent
Keywords: FINGERPRINT; SHUANG-HUANG-LIN; HIGH PERFORMANCE LIQUID CHROMATOGRAPHY; TRADITIONAL CHINESE MEDICINES